2020
DOI: 10.1007/s00467-020-04742-w
|View full text |Cite|
|
Sign up to set email alerts
|

Urine collection methods and dipstick testing in non-toilet-trained children

Abstract: Urinary tract infection is a commonly occurring paediatric infection associated with significant morbidity. Diagnosis is challenging as symptoms are non-specific and definitive diagnosis requires an uncontaminated urine sample to be obtained. Common techniques for sampling in non-toilet-trained children include clean catch, bag, pad, in-out catheterisation and suprapubic aspiration. The pros and cons of each method are examined in detail in this review. They differ significantly in frequency of use, contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 98 publications
1
21
0
1
Order By: Relevance
“…Like these populations, obtaining blood samples for testing in acute bronchiolitis is technically challenging for the healthcare provider and stressful and painful for the patient, especially in cases where repeated tests are needed for monitoring evolution. Evidence shows that it is possible to collect urine non-invasively, efficiently, and quickly, especially in children under three months of age, who constitute most of the hospitalized population with bronchiolitis [22,23]. With this study, we point out that urinary NT-proBNP can be adequately analyzed with the same laboratory kit as serum NT-proBNP (Alere i) in acute bronchiolitis.…”
Section: Feasibility Of Urinary Nt-probnp In Acute Bronchiolitismentioning
confidence: 82%
“…Like these populations, obtaining blood samples for testing in acute bronchiolitis is technically challenging for the healthcare provider and stressful and painful for the patient, especially in cases where repeated tests are needed for monitoring evolution. Evidence shows that it is possible to collect urine non-invasively, efficiently, and quickly, especially in children under three months of age, who constitute most of the hospitalized population with bronchiolitis [22,23]. With this study, we point out that urinary NT-proBNP can be adequately analyzed with the same laboratory kit as serum NT-proBNP (Alere i) in acute bronchiolitis.…”
Section: Feasibility Of Urinary Nt-probnp In Acute Bronchiolitismentioning
confidence: 82%
“…Diviney et al also proposed clean‐catch sampling as the preferred method, because the contamination rate was comparable to invasive methods 26 . Other studies found contamination rates of clean‐catch between 4.5% and 27%, 27–34 whereas Herreros et al 22 reported a contamination rate of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Diviney et al also proposed clean-catch sampling as the preferred method, because the contamination rate was comparable to invasive methods. 26 Other studies found contamination rates of clean-catch between 4.5% and 27%, [27][28][29][30][31][32][33][34] whereas Herreros et al 22 reported a contamination rate of 5%. In addition, the proportion of contamination can be influenced by the criteria used to define contamination, the person performing urine collection, techniques used to reduce contamination or stimulate urination, patient characteristics and setting.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“…The urine dipstick test was immersed into the urine sample to grade the scale of hematuria (from 0–3) in all groups. 18 , 19 …”
Section: Methodsmentioning
confidence: 99%